PENGARUH TINGKAT PENDIDIKAN, KESEHATAN TERHADAP PRODUKTIVITAS DAN JUMLAH PENDUDUK MISKIN DI PROVINSI KALIMANTAN BARAT - ME, HERRY FAISAL (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This Research gets of Influence title Increase Education, Health to Productivity and Indigent Population in West Kalimantan's Province, for 2007 2011 title, by Herry Faisal, Magister's Economics Program of Tanjungpura's University, intent for known influence increases education and health zoom to labouring productivity and numeral beggary at West Kalimantan. Data type that utilized is pane data, namely merging of data traverses place (cross section) and time series data for five years, of 2007 until 2011, with descriptive observational quantitative, by analisis's method bifilar regression, extrapolation tech by LSDV (Least Square Dummy Variable)s methodics. The result observationaling to point out that 1) increase positive influential education (unidirectional) with labouring productivity with regression coefficient as big as 0,138, but bases signifikansi's quiz up to research period point out non relationship signifikan. 2 ) positive influential education zooms and signifikan to productivities with regression coefficient as big as 2,011. 3 ) negative influential education Zooms and signifikan to beggary with regression coefficient 1,273. 4 ) negative influential health Zooms to beggary (excluded is variable) , and 5)influential labouring productivity positive and signifikan to beggary. Base Determinant quiz first equation (R12) as big as 0,458, its mean tries a fall education zoom relationship and health zoom regard productivity as big as 45,8%. Determinant coefficient of second equation (R 2 2 ) among X 1 , X 2 and Y1 to Y2 are 0,889, its mean is level education, health and productivity zoom on 12 region/city regards to increase poverties as big as 88,90%. The Merging Determinant point (Rm2) known as big as 0,6735, its mean all variable that at entry in model give explanation to bonded variable as big as 67,35% meanwhile its rest 32,56% the other influenced that don't at entry in the model. Key word: Education zoom, Health zoom, Productivity welfare, Beggary